PENGARUH PENGEMBANGAN KARIR DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI PADA BADAN PELAKSANAPENYULUHAN DAN KETAHANAN PANGAN KOTA SUNGAI PENUH - Siswadhi, Ferry (Jurnal Benefita, 2017)
The aim of this research was to determine how much influence application leadership and environment work in the office of Gunung Kerinci regency with performance of employee.This research used quantitative method since researcher wanted to determine the measurement of X and Y variable. Population in this study is 32 people. Sampling technique used is a full sampling as many as 17 people. Data analysis techniques in this study ismultiple regresion analysis and coefficient of determination analysis.Questionaires were used as a tool in data collection method. The findings show that all hypothesis were proved to be significant leadership and environment work have a positive and significantinfluence with performance of employee. The implies that played as important roleleadership and environment work (individualy or simultaneously) in developing performance of employee.